Polymorphism of the migration of double-stranded RNA genome segments of avian reoviruses. - Gouvea, V S (1982)
A number of field isolates of avian reovirus were characterized by analysis of the migration pattern of their genomic double-stranded RNA (dsRNA) segments upon polyacrylamide gel electrophoresis. Comparison of the various isolates has demonstrated (i) no relationship between serotype and migration of any individual dsRNA segment, (ii) marked polymorphism of migration patterns of all dsRNA segments among isolates of the same serotype as well as among different serotypes, (iii) no correlation between genotype and disease state, (iv) less marked variability in migration pattern from isolates within a restricted geographic locale compared to isolates from distant locales, (v) the presence of a single genotype in local outbreaks of disease, and (vi) the relative invariant migration of several dsRNA segments among the avian reoviruses, one of which (S1) may serve to distinguish the avian from the mammalian reoviruses.